Relationship Between Anthropometric Profile, Body Composition, and Physical Performance in Spanish Professional Female Soccer Players at Pre-Season Onset: A Cross-Sectional Study - Marta Ramírez-Munera; Raúl Arcusa; Francisco Javier López-Román; Vicente Ávila-Gandía; Silvia Pérez-Piñero; Juan Carlos Muñoz-Carrillo; Antonio Jesús Luque-Rubia; Javier Marhuenda (Journal of Functional Morphology and Kinesiology)
Background: Body composition plays a key role in both anaerobic and aerobic performance in professional soccer. However, its relationship with physical performance in female players remains underexplored. Assessing these parameters at the beginning of the pre-season provides valuable insights for optimizing player readiness. This study investigates the correlation between anthropometric profile, body composition, and physical performance in professional female soccer players at pre-season onset. Additionally, it analyzes positional differences and their relation to the specific physical demands of women’s soccer. Methods: A cross-sectional study of thirty-four female soccer players (age: 23.06 ± 4.29 years, height: 164.15 ± 5.84 cm, weight: 58.39 ± 6.62 kg, and ∑6 skinfolds: 74.57 ± 18.48 mm) who performed anthropometric measurements, the Countermovement Jump (CMJ), Wingate Anaerobic Test (WAnT), and Yo-Yo Intermittent Recovery Level 1 (Yo-Yo IR1) on the first day of the pre-season. One-way ANOVA with Tukey’s post hoc test assessed positional differences, while Pearson’s or Spearman’s correlation coefficients evaluated relationships between anthropometric variables and performance outcomes. Results: Very high positive correlations were found between body and muscle mass with the power variables in CMJ and WAnT (r = 0.70–0.89; p < 0.001). An almost perfect correlation was observed between body mass and peak power in WAnT (r = 0.904; p < 0.001). In contrast, fat mass showed moderate negative correlations with jump height and aerobic performance (Yo-Yo IR1 distance) (r = 0.30–0.49; p < 0.04). Significant differences were observed in the mean (757.60 ± 95.59 W) and peak power (773.59 ± 101.88 W) of CMJ pre-WAnT, with goalkeepers showing higher values compared to defenders and midfielders (p < 0.05). Conclusions: Body composition significantly influences athletic performance, showing positive correlations of muscle and body mass with anaerobic power and capacity. In contrast, fat mass showed negative correlations with explosive strength, recovery, and aerobic capacity.